Amplitude suppression of nongaussian sea clutter in a noncoherent bandpass path of the receiver - E. A. Milashchenko; A. A. Yazovsky (Известия высших учебных заведений России: Радиоэлектроника)
The method of non-linear amplitude suppression of radar clutter from a sea surface in a noncoherent band path of the receiver is considered. The model of the most adequate nongaussian a radar clutter from the rough sea surface which envelope is based on K-distribution of density of probability is used. In model of noises it is considered internal gaussian receiver noise. For various values of parameters of model of clutter amplitude characteristics of a non-linear element and dependence of coefficient of suppression on the relation a clutter/noise are under construction.